Computer organization - Instructional Group Software Research and Development (ISRD Group) (New Delhi, 2007)
This book is an effort to present computer architecture and design in a simple way. A computer consists of various functional modules which coordinate with each other to provide processing needs of the application. The book contains material that provides basics for designing digital electronic circuits and organization of different units of the computer. It also deals with fundamentals of system software.
Keywords: Computer organization